Asking questions in Hmong and other Southeast Asian languages - Clark, Marybeth (2024)
Many of the languages of mainland Southeast Asia share a similar devise for asking yes-no questions, that is, questions such as in (1) which request an affirma¬tive or negative response rather than other information.